Immunocytochemical evidence for co-expression of Type III IP3 receptor with signaling components of bitter taste transduction - Kinnamon Sue C (BMC Neuroscience, 2001)
Abstract Background Taste receptor cells are responsible for transducing chemical stimuli into electrical signals that lead to the sense of taste. An important second messenger in taste transduction is IP3, which is involved in both bitter and sweet transduction pathways. Several components of the bitter transduction pathway have been identified, including the T2R/TRB taste receptors, phospholipase C β2, and the G protein subunits α-gustducin, β3, and γ13. However, the identity of the IP3 receptor subtype in this pathway is not known. In the present study we used immunocytochemistry on rodent taste tissue to identify the IP3 receptors expressed in taste cells and to examine taste bud expression patterns for IP3R3. Results Antibodies against Type I, II, and III IP3 receptors were tested on sections of rat and mouse circumvallate papillae. Robust cytoplasmic labeling for the Type III IP3 receptor (IP3R3) was found in a large subset of taste cells in both species. In contrast, little or no immunoreactivity was seen with antibodies against the Type I or Type II IP3 receptors. To investigate the potential role of IP3R3 in bitter taste transduction, we used double-label immunocytochemistry to determine whether IP3R3 is expressed in the same subset of cells expressing other bitter signaling components. IP3R3 immunoreactive taste cells were also immunoreactive for PLCβ2 and γ13. Alpha-gustducin immunoreactivity was present in a subset of IP3R3, PLCβ2, and γ13 positive cells. Conclusions IP3R3 is the dominant form of the IP3 receptor expressed in taste cells and our data suggest it plays an important role in bitter taste transduction.